Anthropology of law in Muslim Sudan. Land, courts and the plurality of practices - Casciarri, Barbara.; Babiker, Mohamed. (Leiden Studies in Islam and Society, 2018)
Anthropology of Law in Muslim Sudan analyses the hybridity of law systems and the plurality of legal practices in rural and urban contexts of contemporary Sudan, shedding light on the complex relation between Islam and society. It is the outcome of the international research program ANDROMAQUE ( Anthropologie du Droit dans les Mondes Musulmans Africains et Asiatiques ), funded by the French ANR ( Agence National de la Recherche ) between 2011 and 2014. Crossing two disciplinary perspectives, anthropology and law, the present volume contains original fieldwork data on contemporary urban and rural Sudan. Focusing on two major domains, land property and courts, several case studies demonstrate the relevance of an approach based on "legal practices" to underline, first, the plurality and hybridity of law systems and the relative role of the Islamic reference in Sudanese society, and, secondly, the reshaping of legal behaviors and norms after the breaking point of South Sudan's independence in 2011. Contributors are: Zahir M. Abdal-Kareem; Azza A. Abdel Aziz; Musa A. Abdul-Jalil; Munzoul M.A. Assal; Mohamed A. Babiker; Yazid Ben Hounet; Barbara Casciarri; Baudoin Dupret; Philippe Gout; Enrico Ille.